2021
DOI: 10.3748/wjg.v27.i24.3440
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intestinal failure and short bowel syndrome in Crohn’s disease

Abstract: Chronic intestinal failure (CIF) is a rare but feared complication of Crohn’s disease. Depending on the remaining length of the small intestine, the affected intestinal segment, and the residual bowel function, CIF can result in a wide spectrum of symptoms, from single micronutrient malabsorption to complete intestinal failure. Management of CIF has improved significantly in recent years. Advances in home-based parenteral nutrition, in particular, have translated into increased survival and improved quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 162 publications
(192 reference statements)
2
24
1
5
Order By: Relevance
“…Primary BAs are essential nutrients for the growth of C. difficile and can lead to the proliferation of C. difficile . A significant increase in the level of primary BAs at the beginning of weaning has the effect of promoting C. difficile , so it increases the incidence of diarrhea in piglets at the beginning of weaning, which is consistent with Xia Bing’s study [ 32 ]. Xia Bing found that the incidence of diarrhea in the weaning group was 4.63% compared to 0.93% in the lactating group [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…Primary BAs are essential nutrients for the growth of C. difficile and can lead to the proliferation of C. difficile . A significant increase in the level of primary BAs at the beginning of weaning has the effect of promoting C. difficile , so it increases the incidence of diarrhea in piglets at the beginning of weaning, which is consistent with Xia Bing’s study [ 32 ]. Xia Bing found that the incidence of diarrhea in the weaning group was 4.63% compared to 0.93% in the lactating group [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, while optimizing nutritional status may be an effective countermeasure against sarcopenia in IBD, there is currently no established evidence on the role of specific diets or supplements for the prevention and treatment of sarcopenia in IBD. On the other hand, recent advances in nutritional therapy for postoperative short bowel syndrome for Crohn’s disease can inhibit the exacerbation of sarcopenia [ 100 ].…”
Section: Intervention For Patients With Ibd and Sarcopeniamentioning
confidence: 99%
“…The ESPEN guidelines for IBD particularly recommend that CD patients with a proximal fistula and/or a very high output fistula should receive nutritional support by partial or total PN. Since trials show no benefit of PN in the management of acute severe UC, both in terms of inflammatory disease and precolectomy optimization, it is only recommended in malnourished patients with UC and severe disease when EN cannot to be tolerated or oral nutrition or EN are not effective [ 160 , 163 , 164 , 165 ]. As previously mentioned, EN is recommended over PN for use in preoperative optimization [ 5 , 163 , 166 ].…”
Section: Disease-specific Pnmentioning
confidence: 99%